Depletion of abundant plant RuBisCO protein using the protamine sulfate precipitation method. Issue 14 (6th June 2013) - Kim, Yu Ji; Lee, Hye Min; Wang, Yiming; Wu, Jingni; Kim, Sang Gon; Kang, Kyu Young; Park, Ki Hun; Kim, Yong Chul; Choi, In Soo; Agrawal, Ganesh Kumar; Rakwal, Randeep; Kim, Sun Tae
<x xml:space="preserve">Abstract</x> Ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (RuBisCO) is the most abundant plant leaf protein, hampering deep analysis of the leaf proteome. Here, we describe a novel protamine sulfate precipitation (PSP) method for the depletion of RuBisCO. For this purpose, soybean leaf total proteins were extracted using Tris‐Mg/NP‐40 extraction buffer. Obtained clear supernatant was subjected to the PSP method, followed by 13% SDS‐PAGE analysis of total, PS‐supernatant and ‐precipitation derived protein samples. In a dose‐dependent experiment, 0.1% w/v PS was found to be sufficient for precipitating RuBisCO large and small subunits (LSU and SSU). Western blot analysis confirmed no detection of RuBisCO LSU in the PS‐supernatant proteins. Application of this method to Arabidopsis, rice, and maize leaf proteins revealed results similar to soybean. Furthermore, 2DE analyses of PS‐treated soybean leaf displayed enriched protein profile for the protein sample derived from the PS‐supernatant than total proteins. Some enriched 2D spots were subjected to MALDI‐TOF‐TOF analysis and were successfully assigned for their protein identity. Hence, the PSP method is: (i) simple, fast, economical, and reproducible for RuBisCO precipitation from the plant leaf sample; (ii) applicable to both dicot and monocot plants; and (iii) suitable for downstream proteomics analysis.